From Campus to Career: A Qualitative Exploration of Graduate Employability and Workforce Readiness in Ilocos Norte - Eric S Parilla; Jocelyn Evangelista (RSF Press, 2025)
Fresh graduates in Ilocos Norte face substantial impediments while moving from school into the profession, a struggle often rooted in what may be called the epistemological drift of education and industry. An agricultural manager said that a lack of soft-skills training among graduates, especially concerning communication, adaptability, and professionalism, constitutes a major issue in any general setting. Some graduates also have issues with traits or practical experiences peculiar to the industry, as most internship programs are unproductive in developing more contact time and experience in actual working conditions. The gap between the curriculum and industry demands is widening by preparing students inadequately for employment in high-demand sectors such as renewable energy, digital literacy, and environmental planning. Attrition at the graduate level remains a problem in this area because qualified individuals are embarking on outsourcing or mobility toward urban workplaces for higher salaries and more job prospects, thus making the local workforce even more scarce. Addressing such challenges would require better cooperation among educational institutions, industry, and local governments to ensure that programs meet employers' needs. Employers emphasized that micro-credentialing, competency-based training, and structured internships are apparitions to teach students how to teach themselves technical and workplace readiness skills. Career centers should serve as channels for accumulating and providing career advice and relevant professional development workshops to enhance employability. The community would have to revisit compensation schemes and progress in career development to reduce worker flight. The industry-implemented education reforms continued soft-skills training, and the strengthening of academia-industry partnerships will highly impact the likelihood of employability possibilities and the readiness of graduates for the workforce. This summation of strategies can thereafter put Ilocos Norte in a position to develop itself into a locality that hosts the formation of a highly skilled workforce that remains within the local region while supporting sustainable economic growth. Ultimately, the bridging of skill gaps to ensure that fresh graduates transition meaningfully from education to employment remain competitive in the job market, grow their skills in line with industrial demands, and address the ever-evolving requirements of industries.